Hydrogen sulfide induced supramolecular self-assembly in living cells. Issue 65 (27th July 2018) - Wei, Simin; Zhou, Xi-Rui; Huang, Zhentao; Yao, Qingxin; Gao, Yuan
Abstract : A gasotransmitter mediated reduction instructs supramolecular self-assembly in multiple living cell lines, revealing the variation in intracellular H2 S production. Abstract : Here we developed a critical gasotransmitter (H2 S) mediated reduction to induce supramolecular self-assembly in multiple living cell lines. Specifically, the reduction converted an azido group to an amine which allowed the formation of intramolecular hydrogen bonds. The hydrogen bonds planarized the assembling molecules and promoted the supramolecular self-assembly.